PENINGKATAN KEMAMPUAN MENULIS KARANGAN NARASI (CERPEN) DENGAN TEKNIK EMPATIF MAHASISWA PBSI 2013B UNIPA SURABAYA - Sri Budi Astuti; Indayani Indayani (Universitas PGRI Adi Buana Surabaya, 2015)
Abstract In the context of a college education, language teaching known their language skills to be achieved by the students, one of which aspects, namely: writing skills. Based on observations conducted in the 2013 B class PBSI Unipa Surabaya found problems experienced in learning to write. This is an evident from the task of writing a narrative essay (short story) given the lecturer to 35 students in the class, which is only 10 students who achieved the mastery with thoroughness SKM limit specified by study program PBSI of 70, other students have not completed. This was evidenced by the persistence of the students’ difficulties for their ideas in the form of a narrative essay (short story). From the available data indicate that the essay is only 10 students who scored in the top 70, 25 students who have not completed score below 70 is 66. With the use of interesting techniques, learning to write a narrative essay (short story) expected to be more fun and can help students in obtaining ideas (inspiration) when writing a narrative essay (short story). The technique chosen to overcome the difficulties students in writing narrative essay (short story) is empatif technique. The problem in this study is whether the technique can improve the ability to write a narrative essay (short stories) on student PBSI 2013 B Unipa Surabaya? The goal in this research is to improve the ability to write a narrative essay (short stories) with Empatif technique on students PBSI 2013 B Unipa Surabaya. This research is a classroom action research (CAR) using two cycles. Every cycles carried out through four stages: 1) planning, 2) action, 3) observation, 4) reflection. The data collection used were observation and tests. Based on the analysis of classroom activities show that there is improvement in the ability of the student activities in learning to write short stories with empatif technique increased from the first cycle of the average activity carried out 61% to 81% in the second cycle. Based on the analysis of student results a change in an effort to improve the ability to write short stories using techniques empatif, in the first cycle reached 71.43% and increased in the second cycle of 88.57%. Key Words: Writing the narrative, empatif techniques, and short stories.